Televisão digital brasileira : um estudo sobre processos comunicativos e avanços tecnológicos - Vilela, Mateus Dias (2012)
This work aims to study the Brazilian television, analyzing the possibilities that digital technology brings to the middle order to investigate whether these possibilities print new forms of relationships between the TV and the public. Therefore, we will make an analysis of the invention of technology, the first experiments, the three main digital TV standards, the North American, European and Japanese, as well as treat the importance of the television as a source of information and entertainment. We will comment on the relationship between society, technology and the media, observing the form of mutual influence between the three areas. We will additionally, the impact of digital technology on society and the media, with television being the focus of this research. Finally, we analyze the changes in level of resolution and sound, multichannel and multiprogramming, new supports and frameworks, interactivity, mobility and portability in the Brazilian digital TV